Genome-Wide Identification and Characterization of Chinese Cabbage S1fa Transcription Factors and Their Roles in Response to Salt Stress - Ali Anwar; Shu Zhang; Li-Xia Wang; Fengde Wang; Lilong He; Jianwei Gao (MDPI AG, 2022)
The S1fa transcription factor is part of a small family involved in plant growth and development and abiotic stress tolerance. However, the roles of the S1fa genes in abiotic stress tolerance in Chinese cabbage are still unclear. In this study, four S1fa genes in the Chinese cabbage genome were identified and characterized for abiotic stress tolerance. Tissue-specific expression analysis suggested that three of these four S1fa genes were expressed in all tissues of Chinese cabbage, while Bra006994 was only expressed in the silique. Under Hg and Cd stresses, the S1fa genes were significantly expressed but were downregulated under NaCl stresses. The Bra034084 and Bra029784 overexpressing yeast cells exhibited high sensitivity to NaCl stresses, which led to slower growth compared with the wild type yeast cells (EV) under 1 M NaCl stress. In addition, the growth curve of the Bra034084 and Bra029784 overexpressing cells shows that the optical density was reduced significantly under salt stresses. The activities of the antioxidant enzymes, SOD, POD and CAT, were decreased, and the MDA, H2O2 and O2− contents were increased under salt stresses. The expression levels of cell wall biosynthesis genes Ccw14p, Cha1p, Cwp2p, Sed1p, Rlm1p, Rom2p, Mkk1p, Hsp12p, Mkk2p, Sdp1p and YLR194c were significantly enhanced, while Bck1p, and Ptc1p were downregulated under salt stresses. These results suggest that the Bra034084 and Bra029784 genes regulate cell wall biosynthesis and the defense regulatory system under salt stresses. These findings provide a fundamental basis for the further investigation of crop genetic modification to improve crop production and abiotic stress tolerance in Chinese cabbage.